Direct determination of arsenic in acid digests of plant and peat samples using HG-AAS and ICP-SF-MS - Frank, Jutta; Krachler, Michael; Shotyk, William (Analytica chimica acta, 2005)
A new analytical procedure for the reliable and direct determination of arsenic (As) in nitric acid digests of ombrotrophic peat samples in the low ngl−1 range has been developed based on hydride generation-atomic absorption spectrometry (HG-AAS). The pre-reduction capabilities of KI/ascorbic acid and of l-cysteine in nitric acid digests of peat and plant samples for the conversion of As(V) to As(III) were tested systematically. Samples were digested with high purity nitric acid in a high-pressure microwave autoclave at 240°C and subsequently measured using HG-AAS or ICP-SF-MS (inductively coupled plasma-sector field-mass spectrometry). Using KI/ascorbic acid as pre-reductant, the accuracy and precision were poor when digests of complex matrices, such as peat were analyzed for As by HG-AAS. However, 10gl−1l-cysteine was successfully employed as pre-reductant in diluted nitric acid digests (∼3%, v/v) of peat samples prior to hydride generation of As with 0.5% (m/v) of NaBH4 and 7moll−1 HCl. The analytical procedure was critically evaluated by analyzing several certified plant reference materials, two in-house peat reference materials and by the determination of As in diluted digests of peat samples with ICP-SF-MS. The results for the determination of As in various peat and plant materials showed excellent agreement with the reference values. The method detection limits for the determination of As by the optimized HG-AAS procedure and by ICP-SF-MS were 23ngg−1 and 1.4ngg−1 in solid peat, respectively. The newly developed analytical procedure was applied to the determination of As in selected peat samples. Results for As in these peat samples obtained by the developed HG-AAS procedure and the optimized procedure for the determination of As with ICP-SF-MS were highly correlated (R2=0.993, n=12).